Large eddy simulation of premixed hydrogen/methane/air flame propagation in a closed duct. (15th February 2018) - Zheng, Kai; Yu, Minggao; Liang, Yunpei; Zheng, Ligang; Wen, Xiaoping
Abstract: In this paper, large eddy simulation (LES) is performed to investigate the propagation characteristics of premixed hydrogen/methane/air flames in a closed duct. In LES, three stoichiometric hydrogen/methane/air mixtures with hydrogen fractions (volume fractions) of 0, 50% and 100% are used. The numerical results have been verified by comparison with experimental data. All stages of flame propagation that occurred in the experiment are reproduced qualitatively in LES. For fuel/air mixtures with hydrogen fractions of 0 and 50%, only four stages of "tulip" flame formation are observed, but when the hydrogen fraction is 100%, the distorted "tulip" flame appears after flame front inversion. In the acceleration stage, the LES and experimental flame speed and pressure dynamic coincide with each other, except for a hydrogen fraction of 0. After "tulip" flame formation, all LES and experimental flame propagation speeds and pressure dynamics exhibit the same trends for hydrogen fractions of 0 and 100%. However, when the hydrogen fraction is 50%, a slight periodic oscillation appears only in the experiment. In general, the different structures displayed in the flame front during flame propagation can be attributed to the interaction between the flame front, the vortex and the reverse flow formed in the unburned and burned zones. Highlights: Numerical study of premixed hydrogen/methane/air flames propagation is presented. The experimental results are reproduced qualitatively in large eddy simulation. The "tulip" flame formation in hydrogen/methane/air mixtures is different.